THE INFLUENCE OF WORK FAMILY CONFLICT, JOB STRESS, AND WORK ENVIRONMENT ON TURNOVER INTENTION AMONG GARMENT EMPLOYEES AT PT APAC INTI CORPORA - Audy Ulinnuha; Muhammad Bakr Muhlison (Publikasi Inspirasi Indonesia, 2025)
This research was conducted alongside an internship program as part of the academic curriculum at Universitas Islam Indonesia from February 20, 2024, to June 20, 2024. This study aims to examine the influence of work-family conflict, job stress, and work environment on turnover intention. The focus of this research is employees working in the garment division of PT Apac Inti Corpora. The research data were obtained through the distribution of questionnaires to 98 respondents, which were then analyzed using SPSS version 30. The results of the study show that work-family conflict has a positive and significant influence on turnover intention. Job stress also has a positive and significant influence on turnover intention. However, the work environment has a negative and insignificant influence on turnover intention.